Perubahan Kehidupan Sosial Pada Tokoh Utama dalam Novel Room Karya Emma Donoghue - Mutiara Kusuma; Saprudin (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2023)
This research is entitled Changes in Social Life in the Main Character in the Novel Room by Emma Donoghue. This study aims to analyze and find out how changes in social life can occur in the main character in the novel Room by Emma Donoghue. The method that will be used by the researcher in this research is descriptive analysis method. The approach used in reviewing this novel uses a sociology of literature approach. From the results obtained, the changes in social life in this novel are divided into several stages, namely: 1) the social life of the character 2) the twists and turns of the social life of the character 3) the change in the social life of the character 4) the change in the attitude of the character's life 5) improvement in the social change of the character and the last 6) Causes of Changes in Social Characters. From these five stages, the lives of the main characters Joy and Jack change from living their lives in a small room, to living their lives in a free space and a wide world with the help of the local community and the police.